2020
DOI: 10.1155/2020/8820330
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Properties of Rock‐Cemented Coal Gangue‐Fly Ash Backfill Bimaterials with Different Coal Gangue Particle Sizes

Abstract: Properties of rock-cemented coal gangue-fly ash backfill (CGFB) bimaterials determine the effects of strip CGFB mining on controlling the surface subsidence in coal mines, which are affected by the coal gangue particle size in CGFB. In this paper, uniaxial compression tests were conducted on the coarse sandstone-CGFB composite samples with different coal gangue particle sizes, and their strength, acoustic emission (AE), and failure characteristics were investigated. The uniaxial compressive strength (UCS) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The filling materials mainly consisting of different sizes of gangues are essentially a kind of discontinuous media [29][30][31][32], which themselves change in the compaction process.…”
Section: Methodsmentioning
confidence: 99%
“…The filling materials mainly consisting of different sizes of gangues are essentially a kind of discontinuous media [29][30][31][32], which themselves change in the compaction process.…”
Section: Methodsmentioning
confidence: 99%
“…(2) Material and size selection of barricade Regarding the material of the filling barricade, concrete, sand, and gravel can be selected [45,46]. The selection of high-water materials has advantages over other materials due to its fast load-bearing characteristics.…”
Section: Determine the Structure Backfill Mining Parametersmentioning
confidence: 99%
“…Tere are many factors afecting the performance of the flling body. In [10][11][12][13], the authors studied the working performance and uniaxial compressive strength of the mine flling paste with diferent mix ratios and coarse and fne aggregate types. Zhang et al [10] mainly studied the efect of diferent watercement ratios on the performance of iron ore tailings flling paste.…”
Section: Introductionmentioning
confidence: 99%
“…Trough testing its workability and strength, it was found that the optimal water-cement ratio was 0.4, but the general applicability was not known. Wang et al [11] analyzed the change of strength by changing the particle size of coal gangue in rock glue gangue fy ash fllings, and found that the increase of coal gangue particle size would lead to the decrease of flling body strength. Jia and Feng [12] and Feng et al [13] used waste concrete as fne aggregate and coarse aggregate, respectively, to replace coal gangue to prepare flling paste and studied the infuence of waste concrete coarse and fne aggregate on the performance of flling paste from the perspective of working performance and uniaxial cubic compressive strength.…”
Section: Introductionmentioning
confidence: 99%